Assessment of Preterm Infants Using the Bayley-III Scales in Korea - Ahn, Sung Ho (Ann Rehabil Med, 2017)
OBJECTIVE: To assess the well-being of preterm newborns using the Bayley-III scales in a Korean-based population, and to evaluate the perinatal risk factors influencing developmental outcome. METHODS: Using the Bayley-III scales, we assessed 120 preterm infants who were referred for evaluation of neurodevelopmental performance. We subdivided them into an extremely preterm group (n=18) and a very/moderate to late preterm group (n=102). Bayley-III mean scores and the rate of infants showing a delay were compared for both groups. The relationship between perinatal risk factors and Bayley-III scores was analyzed. The risk factors were considered as very low birth weight, history of neonatal medical problems, and abnormal radiologic findings in brain magnetic resonance images (MRIs). RESULTS: Although no significant differences in mean scores were observed between the extremely preterm group and the very/moderate to late preterm group, the rate of babies showing developmental delay in motor composite scores was significantly higher in the extremely preterm group. The proportions of preterm infants with cognitive, language, and motor delays were 38.3%, 26.7%, and 35.0%, respectively. Very low birth weight was a significant risk factor for low cognitive, language, and motor composite scores. Also, abnormal radiologic findings on brain MRI were significant indicators of lower motor composite scores. CONCLUSION: Cognitive development was the most frequently delayed domain in preterm infants and motor development was more frequently delayed in the extremely preterm group. The very low birth weight and abnormal radiologic findings in brain MRI were predictive factors for neurodevelopmental outcome.